European studies on prevalence and risk of autism spectrum disorders according to immigrant status—a review - Kawa, Rafał; Saemundsen, Evald; Lóa Jónsdóttir, Sigrídur; Hellendoorn, Annika; Lemcke, Sanne; Canal-Bedia, Ricardo; García-Primo, Patricia; Moilanen, Irma (European journal of public health, 2017)
Autism spectrum disorders (ASDs), once considered to be rare, are now reaching prevalence estimates of 1% and higher. Studies conducted in North America indicate large racial/ethnic disparities in the diagnosis of ASDs. Others show, that immigrant children have similar prevalence rates of ASDs as native children, although they are diagnosed later compared with native children. In relation to a EU funded network action, Enhancing the Scientific Study of Early Autism, it was considered important to review the literature on this subject. A comprehensive literature search was undertaken for original articles reporting on prevalence and risk for ASD in Europe among immigrants and ethnic minorities and data across studies were compared. Seventeen studies conducted in Europe concerning immigrants and ethnic minorities were found. Fifteen studies suggest a higher prevalence rate of ASDs among children of immigrants in comparison to native children (RR = 1.02-1.74; OR = 0.6-10.5). One study revealed higher prevalence of autism (OR = 2.2; 95% CI 1.6-3.1) and lower prevalence of Asperger syndrome in immigrants (OR = 0.6; 95% CI 0.3-0.97). One study showed a lower prevalence of Asperger syndrome in immigrants (aOR = 0.1, 95% CI 0.01-0.5). The majority of those analyses involved immigrants from outside Europe, e.g. from Africa and South America. After analysing the results of studies conducted in Europe, it is unclear if higher prevalence estimates of ASDs among immigrants in this region reflect true differences, especially considering many potential confounding factors, e.g. genetic, biological, environmental and cultural. Considering the number of people migrating within Europe there is a substantial need to study further the prevalence of ASDs in immigrant groups.